Imagens do Brasil: o Cinema Novo e as metamorfoses da identidade nacional - Malafaia, Wolney Vianna (2012)
This paper aims at analyzing cinema cultural politics and its relation to national identity, which developed between the end of the 50’s and the beginning of the 80´s. The main agents of this process are the filmmakers linked to Cinema Novo and the authoritarian State, implemented from 1964 on, having the deep modernization process experienced by the Brazilian society in this period as its background. Among the sources used, the cinema production in this period is highlighted, due to its importance in the understanding both of the ideas formulated about national identity and of the contradictions inherent in this process. In the first chapter, we analyze the genesis of Cinema Novo, recognizing it as a cultural and political movement, establishing its sociability networks and characterizing its aesthetic and political aspects common to filmmakers who took part in it. This analysis considered three different moments: the first, between 1955 and 1964, when the genesis of Cinema Novo took place; the second, between 1964 and 1968, when Cinema Novo met its apex and consolidated itself as cultural and political proposal; and the third, between 1969 and 1973, when the aesthetic proposal was extinguished, giving room to the political articulations and to the individual proposals that characterized this cultural movement until the beginning of the 80’s. In the second chapter, the main objective of the analysis is the action of the authoritarian State, established from 1964 on, in the field of culture. We consider in retrospect the interventions of Brazilian State in this field up to 1964; we discuss the attitude of the authoritarian State towards cultural production and highlight the Culture National Policy, presented in the end of 1975, the main reference to understanding the process of construction of the national identity in the transition period. In the third chapter, we specifically analyze the cinema cultural politics from 1974 on, its aspects in common with Culture National Policy and its contradictions in relation to the action of the authoritarian State in the cultural area and to the modernization process through which Brazilian society has gone. Through this analysis, we try to understand the way cinemanovistas and representatives of official organs of the cultural area noticed the running of a cinema cultural politics that met the needs of this transition period ad supplied the elements to the construction of national identity. In the fourth chapter, we analyze the path of Joaquim Pedro de Andrade as cinemanovista intellectual, deeply influenced by modernist ideals of the 20´s and 30´s, and critical of the authoritarian modernization process put into practice from 1964 on. We regard the path and work of this filmmaker as paradigmatic, not only in relation to the complex cultural and political links developed by Cinema Novo, but also in relation to the deep changes experienced by the Brazilian society in that period. Between 1955 and 1982, several political proposals for the cultural area were developed, two of them worth of notice: the one made and presented by Cinema Novo and the one related to the intervention of the authoritarian State in this area. The action of cinemanovistas intellectuals and the dialogue established between them and their interlocutors, representatives of the authoritarian State in the field of culture, have made the construction of a national identity in times of transition possible, corroborating the redemocratization process and building new ways of seeing, analyzing and understanding Brazilian society.